New Testament introduction - Guthrie, Donald, 1916- (London, UK Tyndale, 1970)
Includes bibliographical references and indexes.
Originally published in 3 vols : The Gospels and Acts, 1965; The Pauline Epistles, 1961 ; Hebrews to Revelation, 1962 (2nd ed. 1964) : all of which, see also.
Keywords: Bible N.T. -- introductions